Clinical effectiveness of sodium hyaluronate gel usage for prevention of postoperative adhesion in children - A.A. Kvashnina; M.G. Melnychenko; V.F. Rybalchenko (Group of Companies Med Expert, LLC, 2022)
It was considered expedient to study the effectiveness of intraoperative prevention of adhesion formation in children based on the results of our own experimental and clinical studies on the effectiveness of using an anti-adhesive gel based on cross-linked sodium hyaluronate. Purpose - to evaluate clinical efficacy and safety of cross-linked sodium hyaluronate gel (SHG) usage as a barrier agent for primary prevention of postoperative peritoneal adhesions formation in children. Materials and methods. This is a prospective, randomized, controlled, patient blinded observational study, which includes 62 children. All patients underwent laparotomy for appendicular peritonitis and were randomly divided into two equal groups. Patients from group A (n=31) received conventional surgical treatment, SHG was additionally applied in group B (n=31) before abdominal closure. Immediate and long-term effects of SHG usage were investigated to evaluate the influence on adhesions reformation. The average period of postoperative observation was 14.0±2.4 months. Results. SHG application was associated with no increase in complications rate: duration of postoperative ileus, need in nasogastric decompression, intensive care unit state, hospital state, the incidence of surgical site infection, and need for relaparotomy did not differ significantly between compared groups. The prevalence of peritoneal adhesions at the end of in-hospital treatment differs significantly between groups according to the ultrasound data (χ2=10.930; p=0.005). The incidence of small bowel obstruction (SBO) developed during the follow-up period in group A (16.1%) was significantly higher than in group B (3.23%) where the anti-adhesive gel was applied (χ2=4.026; p=0.045). Conclusions. Intraoperative use of SHG based on sodium hyaluronate allows reduction of postoperative adhesions formation in children without worsening the postoperative course. The research was carried out in accordance with the principles of the Helsinki declaration. The study protocol was approved by the Local ethics committee of all participating institutions. The informed consent of the patient was obtained for conducting the studies. No conflict of interests was declared by the authors.